Legal Perspectives on State Responsibility in Transboundary Environmental Pollution (International Forum of Researchers and Lecturers, 2025)
Transboundary environmental pollution poses significant challenges in international law, particularly regarding state responsibility. This study examines the legal frameworks governing state liability for environmental damage that extends beyond national borders. The research explores key principles such as the